Terrorism and the Media: The Effect of US Television Coverage on Al-Qaeda Attacks - Michael Jetter (Institute of Labor Economics (IZA), 2017)
Can media coverage of a terrorist organization encourage their execution of further attacks? This paper analyzes the day-to-day news coverage of Al-Qaeda on US television since 9/11 and the group's terrorist strikes. To isolate causality, I use disaster deaths worldwide as an exogenous variation that crowds out Al-Qaeda coverage in an instrumental variable framework. The results suggest a positive and statistically powerful effect of CNN, NBC, CBS, and Fox News coverage on subsequent Al-Qaeda attacks. This result is robust to a battery of alternative estimations, extensions, and placebo regressions. One minute of Al-Qaeda coverage in a 30-minute news segment causes approximately one attack in the upcoming week, equivalent to 4.9 casualties, on average.
Keywords: C26; D74; F52; L82; 330; Al-Qaeda; media attention; media effects; terrorism; 9/11